The Use of Robotic-Assisted Total Hip Arthroplasty in Developmental Dysplasia of the Hip - Jonathan M. Vigdorchik, MD; Abhinav K. Sharma, BS; Vinay K. Aggarwal, MD; Kaitlin M. Carroll, BS; Seth A. Jerabek, MD (Arthroplasty Today, 2020)
Background: Total hip arthroplasty (THA) is an effective operation for patients with hip osteoarthritis; however, patients with hip dysplasia present a particular challenge. Our novel study examined the effect of robot-assisted THA in patients with hip dysplasia. Methods: We retrospectively reviewed patients with developmental dysplasia of the hip undergoing primary THA using robotic arm assistance at 2 institutions from January 2010 to January 2017. Patients undergoing revision arthroplasty were excluded. Preoperatively, all patients underwent a computed tomography scan so that 3-dimensional templating could be performed. Hip range of motion (ROM) and clinical leg length discrepancy were recorded preoperatively. Two independent observers calculated Crowe and Hartofilakidis grades for each operative hip. At the final follow-up, hip ROM, postoperative complications, and modified Harris Hip scores were obtained. Results: Seventy-nine patients underwent THA because of degenerative joint disease in the setting of developmental dysplasia of the hip. There were 56 females and 23 males with a mean age of 45 years (range: 26-64 years). We found that components were placed according to the preoperative plan, that there was an improvement in the modified Harris hip score from 29 to 86 (P < .001), an improvement in the hip ROM (flexion improvement from 66° to 91°, P < .0001), and a correction of leg length discrepancy (17.1 vs 4 mm, P < .0002). There were no complications during the short-term interim follow-up (mean: 3.1 years). Conclusions: Robot-assisted THA can be a useful method to ensure adequate component positioning and excellent outcomes in patients with hip dysplasia. Level of Evidence: Level III, Retrospective